Research advances of obinutuzumab in the treatment of membranous nephropathy - Xiao-jing Lin; Jing Sun; Hao-yi Xiangli; Xuan-yi Du (Linchuang shenzangbing zazhi, 2024)
Membranous nephropathy （MN） is a common cause of adult nephrotic syndrome. Rituximab, a type Ⅰ anti-CD20 monoclonal antibody, is an effective treatment of MN. However, its response rate is merely 60% during a follow-up period of up to 24 months. Obinutuzumab is a type Ⅱ humanized anti-CD20 monoclonal antibody modified by glycosylation. As compared with rituximab, it can cause a more severe depletion of B lymphocyte so as to demonstrate a better efficacy for some hematological malignancies. Currently obinutuzumab is applied for lupus nephritis and kidney transplantation. Based upon its definite efficacy, some centers have promoted using obinutuzumab for MN. This review summarized the clinical application of obinutuzumab.